Gαs, adenylyl cyclase, and their relationship to the diagnosis and treatment of depression - Schappi, Jeffrey M.; Rasenick, Mark M. (Frontiers in Pharmacology, 2022)
The relationship between depression, its etiology and therapy, and the cAMP signaling system have been studies for decades. This review will focus on cAMP, G proteins and adenylyl cyclase and depression or antidepressant action. Both human and animal studies are compared and contrasted. It is concluded that there is some synteny in the findings that cAMP signaling is attenuated in depression and that this is reversed by successful antidepressant therapy. The G protein that activates adenylyl cyclase, Gαs, appears to have diminished access to adenylyl cyclase in depression, and this is rectified by successful antidepressant treatment. Unfortunately, attempts to link specific isoforms of adenylyl cyclase to depression or antidepressant action suffer from discontinuity between human and animal studies.